The effect of aging treatment on the fracture toughness and impact strength of injection molded Ni-625 superalloy parts - GÜLSOY, HAMİT ÖZKAN (ELSEVIER SCIENCE INC, 2015)
In this study, the effect of aging heat treatment on fracture toughness and impact strength of Ni-625 superalloy fabricated by using powder injection molding (PIM) method was examined. After a feedstock was prepared by mixing the prealloyed Ni-625 superalloy powder, which was fabricated by gas atomisation, with a polymeric binder system and then it was granulated, it was shaped through the use of injection. The molded specimens were sintered at 1300 degrees C for 3 h after a two-stage debinding process. Once the sintered specimens were treated in the solution at 1150 degrees C for 2 h, they were quenched. Aging treatment was performed by keeping specimens at 745 degrees C for 22 h. Fracture toughness and impact tests were performed on sintered and aged specimens. Microstructure examinations were performed by using optical microscope, scanning electron microscope, and transmission electron microscope. The results revealed that aging heat treatment led to the formation of some carbides and intermetallic phases in the microstructure. While the hardness of the aged specimens increased due to these phases, their fracture toughness and impact strength values decreased. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Ni-based superalloy; Aging; Fracture toughness; Impact toughness; Carbides; Intermetallic phases; MECHANICAL-PROPERTIES; SINTERED STEEL; MICROSTRUCTURE; FATIGUE